An Improvement on Kim's Inequality for Pricing Asian Option (Advances in Systems Science and Applications, 2012)
In his study of a simple one-dimensional parabolic PDE, Kim[11] obtained an inequality that the price of Asian options satisfies. This paper aims to improve this particular Kim’s inequality. Our inequality has an advantage over Kim’s, for our estimation has an upper bound as R vanishes. Therefore, our newly established estimation can help us to determine the solution error of a second order partial differential equation with variable coefficients.